Local community perception towards ecotourism activity at Bukit Bakar and Jeram Linang Recreational Forest, Kelantan - Masri, Muhammad Irfan (2019)
Concerned with the decreasing number of visitors towards the Bukit Bakar and Jeram Linang recreational forest, the Department of Forestry Kelantan took the responsibility in re-developing the recreation forest as ecotourism site to attract visitors. The present study determines the local community perception towards the ecotourism activity at Bukit Bakar recreational forest and Jeram Linang recreational forest. A qualitative research is used to understand and determined their perception towards ecotourism activity and involvement. Results from the study showed that the local community have positive perception towards ecotourism activity at Bukit Bakar and Jeram Linang recreational forest as it provides high business opportunity to the local community. The result also show that people in the community mostly work depending on the recreation forest as their main income. Moreover, local community also perceive that the safety of the facilities in Bukit Bakar and Jeram Linang recreational forest are in worried situation. The facilities of the recreational forest show differently as it need maintenance and the visitors hope it been rebuilt. As conclusion, the local community in Bukit Bakar and Jeram Linang give positive impact in redeveloping the recreational forest as ecotourism site in the area.